2006
DOI: 10.1042/bc20050101
|View full text |Cite
|
Sign up to set email alerts
|

The human orthologue of CdGAP is a phosphoprotein and a GTPase‐activating protein for Cdc42 and Rac1 but not RhoA

Abstract: Background information. Rho GTPases regulate a wide range of cellular functions affecting both cell proliferation and cytoskeletal dynamics. They cycle between inactive GDP-and active GTP-bound states. This cycle is tightly regulated by GEFs (guanine nucleotide-exchange factors) and GAPs (GTPase-activating proteins). Mouse CdGAP (mCdc42 GTPase-activating protein) has been previously identified and characterized as a specific GAP for Rac1 and Cdc42, but not for RhoA. It consists of an N-terminal RhoGAP domain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Mouse and hCdGAP constructs were as described previously (Southgate et al, submitted;Tcherkezian et al, 2005Tcherkezian et al, , 2006.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse and hCdGAP constructs were as described previously (Southgate et al, submitted;Tcherkezian et al, 2005Tcherkezian et al, , 2006.…”
Section: Methodsmentioning
confidence: 99%
“…CdGAP contains a N-terminal GAP domain, a basic central region and a proline-rich domain (PRD) with an extended C-terminal domain (Lamarche-Vane and Hall, 1998;Jenna et al, 2002;Tcherkezian et al, 2006). We have previously shown that CdGAP is a substrate of ERK/GSK-3 and mediates cross talk between the Ras/MAP kinase pathway and regulation of Rac1 activity (Tcherkezian et al, 2005;Danek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is required for cell spreading, polarized lamellipodia formation and cell migration. 14,15 The Rho GTPases control many aspects of cell behavior, such as the organization of the cytoskeleton, cell migration, cell-cell and cell-matrix adhesion, cell-cycle progression, gene expression and cell polarity. [16][17][18] DLG1-disks, large homolog 1…”
Section: Hpa036380mentioning
confidence: 99%
“…DNA Constructs-CdGAP constructs were as described previously (6,8,11). GSK-3␣ was obtained as a full clone in the pACTII vector (see "Yeast Two-hybrid Screen").…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant GSK-3␣ and -␤ and phospho-glycogen synthase peptide were purchased from Upstate Biotechnology. Polyclonal anti-CdGAP antibodies were produced and purified as described previously (8,11). Polyclonal antibodies against phospho-Thr-776 of CdGAP were produced by immunizing rabbits with a peptide CXPPPPT*PLEEEPE (T* represents phosphorylated threonine, and X represents hexanoic acid spacer).…”
Section: Methodsmentioning
confidence: 99%